1990
DOI: 10.4141/cjps90-134
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Volunteer Wheat and Barley on the Growth and Yield of Flax

Abstract: . Effects of volunteer wheat and barley on the growth and yield of flax. Can. J. Plant Sci. 70: 1115-1122. Fieid experiments were conducted in 1982 and 1983 to determine the effects of increasing densities (0-70 plants m '.; (Anonymous 1986(Anonymous , 1987b. Recent weed surveys confirm that volunteer wheat and barley commonly occur as weeds in flax fields (Thomas and Wise 1983.Flax is well known for being a poor competitor with weeds (Friesen and Shebeski 1960;Dew 1972). Bowden and Friesen (1967) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…In this study, a 5% corn yield reduction occurred with a volunteer wheat density of 5.2 plants m (2 . Similar yield losses caused by volunteer wheat have been reported in flax (Friesen et al 1990) and canola (O'Donovan 1992). Table 3.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…In this study, a 5% corn yield reduction occurred with a volunteer wheat density of 5.2 plants m (2 . Similar yield losses caused by volunteer wheat have been reported in flax (Friesen et al 1990) and canola (O'Donovan 1992). Table 3.…”
Section: Resultssupporting
confidence: 54%
“…Volunteer wheat and barley reduced flax yields by 49 to 63% (Friesen et al 1990). Marshall et al (1989) reported that volunteer wheat and barley at densities of 30 plants m (2 caused a 17 and 35% yield reduction in rapeseed (Brassica napus L.), respectively.…”
mentioning
confidence: 99%
“…Although annual flax acreage has not changed to any extent over the past two decades, the relative abundance of volunteer flax has increased from 2.0 to 15.3 over the same period (Thomas et al 1997). While volunteer cereals in flax are known to reduce flax yields (Friesen et al 1990), reduction of wheat yields by volunteer flax has not been recorded. Discussions with producers suggest that volunteer flax is more of a problem for those using zero-tillage than conventional production systems.…”
mentioning
confidence: 99%
“…Flax and barley dry weights (DW) were determined by drying in an oven to constant weight at 80°C, Where appropriate, seed heads of barley and seed bolls of flax were collected and dried separately. Two separate harvests were conducted, HI at the end of July (1990 only), coincident with high quality fibre production (flowering) and H2, at the end of August (1989 and1990), coincident with maximum fibre yield together with the production of mature seed boUs.…”
Section: Assessmentsmentioning
confidence: 99%
“…In Imseed, competition by volunteer wheat and barley at densities of 30 plants m~^ has been shown to reduce seed yield by 50 and 60% respectively (Friesen et al, 1990), It has been pointed out, however, that to extrapolate research findings between flax and linseed is seldom prudent (Lutman, 1991) since the culture and growth of the two differ. Furthermore, the majority of such competition and weed-control studies have been conducted in dryland farming conditions and are inappropriate to the moist, cool climates under which fibre flax is frequently grown.…”
Section: Introductionmentioning
confidence: 99%